Genomic persistence of Listeria monocytogenes strains in dairy and meat processing plants in Italy. (20th October 2021) - Acciari, VA; Del Matto, I; Antoci, S; Di Marzio, V; Torresi, M; Iannetti, L; Marfoglia, C; Centorotola, G; Pomilio, F
Abstract: Background: Persistence of Listeria monocytogenes (Lm) in food processing plants (FPP) is still considered the major source of food contamination during processing. Correlations among different Lm strains and evaluation of the isolates persistence in FPP environments is an essential tool to improve food safety. The aim of this study was to investigate the genomic characteristics of persistent Lm strains (e.g. Metal and Detergent Resistance, SSIs and genomic island). Methods: Totally 221 strains isolated from 10 FPP in the Abruzzo and Molise regions, Italy, were enrolled (4 of dairy products FPP - DP - and 6 of meat products FPP - MP). Sampling was performed in 6 sessions, from March 2017 to May 2018. Strains were sequenced using Illumina platform. The CCs, cgMLST analysis and Metal and Detergent Resistance, SSIs and genomic island (GI) detection was carried using the Pasteur scheme. Results: Results returned 13 CCs and 2 singletons. cgMLST clustering showed two persistent clusters DP and 9 clusters in MP. In DP CC3 and CC9 were persistent. While in MP CC5, CC8, CC9, CC37, CC121 and CC155. The presence of SSI-1, was detected in 100% of the persistent strains from DP and 80% from MP, in particular in all strains of CC155, CC5, CC8 and CC9. In CC121 and CC37 it was absent. The presence of loci of Lm GI3, was in 100% of persistent strains of DP and in 52.3% of MP plant, in particular in 100% of CC121, CC8, CC5 and 16.3% of CC9. The 100% of CC121 in DP and MP plant harboured Tn6188 and SSI-2. The inlA PMSC mutations were detected in 100% of CC9 and CC121 strains. Conclusions: The persistence of strains inside FPP was confirmed using NGS data, most of the strains were characterised by the presence of genes involved in resistance and adaptation. NGS is confirmed to be a powerful tool to study Lm persistence in FPP, looking also at strains' ecology. Key messages: Most of persistent strains showed genes involved in resistance and adaptation in the food processing environment. NGS could help in facing Lm persistence in food producing plants giving new insights on the genomic characteristics of persistent strains.